Fashion industry and tourism strategy : transforming destinations and shaping experiences - Valeri, Marco; Asthana, Shekhar (Emerald Publishing Limited, 2025)
Fashion Industry and Tourism Strategy: Transforming Destinations and Shaping Experiences explores the growing intersection between fashion events and tourism, highlighting their socio-economic contributions to global destinations. Once limited to showcasing clothing, fashion events have evolved into a key driver of luxury tourism, influencing travel patterns, consumer behaviour, and destination branding. The increasing interest in luxury lifestyles, particularly in developing economies, has fuelled a surge in travellers to iconic fashion capitals such as Paris, Milan, and New York. While research has acknowledged the economic significance of fashion tourism, critical gaps remain in understanding its broader impact, including its role in cultural exchange, destination image-building, and sustainability. In addition to economic considerations, this contributed work delves into the socio-environmental implications of fashion tourism, assessing its influence on heritage conservation, commercialisation, and sustainable development. The potential of fashion tourism to revitalise emerging destinations and serve as an off-season tourism strategy is explored, alongside concerns about overconsumption, resource exploitation, and social inequalities in the fast-fashion industry. Through a multidisciplinary approach, encompassing organisational behaviour, finance, psychology, social development, and operations, Fashion Industry and Tourism Strategy: Transforming Destinations and Shaping Experiences fresh insights into an evolving tourism segment, making it a valuable resource for scholars, industry professionals, and policymakers.